2021
DOI: 10.1021/acsaem.1c00357
|View full text |Cite
|
Sign up to set email alerts
|

Chalcogenide Dopant-Induced Lattice Expansion in Cobalt Vanadium Oxide Nanosheets for Enhanced Supercapacitor Performance

Abstract: We explore the effect of sulfur doping in Co 3 V 2 O 8 on the electrochemical performance of supercapacitors in terms of enhanced lattice spacing, electrochemical surface area (ECSA), electronic conductivity, and density of states. The sulfur-doped Co 3 V 2 O 8 (S-Co 3 V 2 O 8 ) nanosheets were grown in situ as a binderfree synthesis on nickel foam by the hydrothermal method. The electrochemical performance was analyzed in an aqueous alkaline electrolyte where the S-Co 3 V 2 O 8 electrode exhibited a specific … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(8 citation statements)
references
References 69 publications
0
8
0
Order By: Relevance
“…S14c † exhibits the V 2p spectrum with the V 5+ and V 4+ states, indicating its steady valence state. 39 The Ti 2p spectrum in Fig. S14d † suggested the existence of Ti 3 C 2 T x MXene.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…S14c † exhibits the V 2p spectrum with the V 5+ and V 4+ states, indicating its steady valence state. 39 The Ti 2p spectrum in Fig. S14d † suggested the existence of Ti 3 C 2 T x MXene.…”
Section: Resultsmentioning
confidence: 95%
“…S14b † revealed the presence of Co 2+ and Co 3+ , but the weaker Co 2+ and satellite peaks compared to the pre-cycling indicated that Co 2+ was partially converted to Co 3+ , which agreed with the observations in the previous literature. 39 Fig. S14c † exhibits the V 2p spectrum with the V 5+ and V 4+ states, indicating its steady valence state.…”
Section: Resultsmentioning
confidence: 98%
“…S8†) and are summarized in Table S7 †48,49 The calculated value of ECASA for the NNMO-3 electrode is 9650 cm 2 , which is significantly larger than those of the other nanocomposite electrodes (NNMO-1: 6031 cm 2 , NNMO-2: 6863 cm 2 , and NNMO-4: 3949 cm 2 ), and therefore, signifies the higher availability of the electroactive sites for better capacitive behaviour among all the tested nanocomposite electrodes. 49 The maximum bulk BET specific surface area along with the mesoporous structure (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The replacement of the oxygen with sulphur decreases the diffraction angle due to the increased d spacing. 33…”
Section: Resultsmentioning
confidence: 99%
“…Recently, Sharma et al reported that the doping of sulphur in Co 3 V 2 O 8 results in the improved conductivity of Co 3 V 2 O 8 . 33 As the change in conductivity alters the surface energy of the catalyst, S-Co 3 V 2 O 8 exhibits better OER performance. Additionally, the oxygen vacancies created due to vanadium in Co 3 V 2 O 8 further support the OER.…”
Section: Resultsmentioning
confidence: 99%